(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: The aim of this study is to find significance between mode of delivery and the pre-ductal and post-ductal oxygen saturation levels in healthy term neonates in 1st 10 minutes on life. Method: Healthy term newborns between 37weekes to 42 weeks, who do not require any resuscitation measures were included in the study. Continuous recording was done using pulse oximetry in 1st 10 minutes of life. Result: The mean time taken to reach preductal sp02 to 90% in LSCS is 7.3 +/-0-58 mins and in normal vaginal delivery it takes 6+/-0.78 mins to reach 90%. The mean time taken to reach postductal SPO2 to 90% in LSCS babies is 8.1+/-0.68 mins and in it takes 7.1+/-0.86 mins to reach 90% in normal vaginal delivered neonates. Conclusion: Pre-ductal and post-ductal spo2 is significantly lower in babies delivered by LSCS when compared to vaginal delivery, there is significant difference in time reaching spo2 level of 90% or above in pre-ductal and post-ductal sites in babies delivered via LSCS compared to normal delivery.